Mental health and mental toughness in biathlon: Practical implications from the coaches` viewpoint - Plesser, M.; Finkenzeller, T.; Bernatzky, P. (Journal of Biathlon Coaching, 2025)
In the high-pressure domain of competitive sport, biathletes are recognized for their exceptional physical capabilities and mental toughness. However, increasing awareness of mental health challenges among elite athletes has prompted a critical examination of the dynamic interplay between mental toughness and mental health in sustaining long-term athletic success (Gucciardi, Hanton, & Fleming, 2017). While closely interrelated, these constructs represent distinct domains that necessitate differentiated and individualized approaches in the psychological support and care of athletes. Understanding this distinction is essential for developing holistic performance models that prioritize both competitive excellence and athlete well-being.